2007
DOI: 10.3354/meps330201
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of whiting Merlangius merlangus in the northeast Atlantic and adjacent waters

Abstract: Accurate identification of stock boundaries is essential for efficient fisheries management; hence, the present study focused on the genetic structure of whiting. To this aim, 488 individuals collected from the southern Bay of Biscay to the southern Norwegian coast were genotyped using 7 microsatellites. A low level of genetic structuring was detected in Atlantic waters; only the Bay of Biscay differentiated from more northern samples. The lack of genetic structure along the western margin of the British Isles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 36 publications
4
23
0
Order By: Relevance
“…Whiting is caught as part of a mixed fishery operating in the North Sea throughout the entire year, and is currently managed and assessed as a single unit (Table 2). However, significant genetic structuring was recently found in the North Sea, which is relatively similar to that found for cod (Hutchinson et al 2001), with three distinct whiting populations in the areas of the Southern Bight, the Flamborough Head and the Dogger Bank/Norwegian coast (Charrier et al 2007). The temporal stability of the genetic population differentiation is not yet assessed, but previous studies of parasitic infestation and tagging data also suggested population differentiation within the North Sea (e.g.…”
Section: Other Demersal Roundfish Speciessupporting
confidence: 60%
See 1 more Smart Citation
“…Whiting is caught as part of a mixed fishery operating in the North Sea throughout the entire year, and is currently managed and assessed as a single unit (Table 2). However, significant genetic structuring was recently found in the North Sea, which is relatively similar to that found for cod (Hutchinson et al 2001), with three distinct whiting populations in the areas of the Southern Bight, the Flamborough Head and the Dogger Bank/Norwegian coast (Charrier et al 2007). The temporal stability of the genetic population differentiation is not yet assessed, but previous studies of parasitic infestation and tagging data also suggested population differentiation within the North Sea (e.g.…”
Section: Other Demersal Roundfish Speciessupporting
confidence: 60%
“…However, significant genetic structuring was recently found in the North Sea, which is relatively similar to that found for cod (Hutchinson et al . 2001), with three distinct whiting populations in the areas of the Southern Bight, the Flamborough Head and the Dogger Bank/Norwegian coast (Charrier et al . 2007).…”
Section: Mismatch Between Management and Biological Units In The Ne Amentioning
confidence: 99%
“…Our findings have important implications from a fisheries management perspective because an accurate definition of population boundaries constitutes the basis for ensuring the viability of exploited marine resources through coherent management plans, and a failure to identify population structure could lead to overfishing of some stock components and ultimately to the erosion of genetic diversity at the species level through local population depletions or extinctions (Charrier et al 2007). Although the three groups showed genetic heterogeneity temporarily, human-aided translocation of individuals, presumably in ballast water and transfer of juvenile gastropods by farmers, can mimic the effects of natural dispersal and thus would eliminate the genetic differentiation between populations over a longer time scale.…”
Section: Discussionmentioning
confidence: 96%
“…However, these diVerences were not temporally stable, likely due to transient dispersal events into the Channel and subsequently the North Sea. A lack of strong and stable diVerentiation between the Irish Sea and North Sea has also been documented for other North Atlantic Wsh such as plaice ), turbot (Hemmer-Hansen et al 2007a and whiting (Charrier et al 2007). Finally, the overall very low genetic divergence among sole populations within the North Sea is consistent with other marine Wsh (Borsa et al 1997;Hemmer-Hansen et al 2007a, b;Hoarau et al 2002;Nielsen et al 2004).…”
Section: Population Structurementioning
confidence: 88%